Developing academic vocabulary with AWL gapmaker and corpus data - Križan, Agata (Vestnik za tuje jezike, 2009)
There is a growing need for the development of at least some academic vocabulary in students of EFL (studying English for teaching and non-teaching purposes), if one of the main aims of EFL study is to produce competent users of English. Students are expected to read and understand advanced professional texts, not simply to successfully complete their degrees but to become a part of educated society, and to be able to meet the demands placed upon their knowledge in a prefessional environment. The reading and understanding of professional texts can be a highly demanding activity because of the number of academic and professional terms such texts include. This paper exemplifies the usefulness of a gap-fill exercise, as one among a range of options for developing and testing academic vocabulary in a professional context. The exercise was compiled with AWL gapmaker based on a professional review text, which includes academic items of vocabulary. The gap-fill exercise was used with two groups of EFL students in the same year of study and installed at two difficulty levels for two reasons: to test students' existing knowledge of academic vocabulary, and to enrich it through the analysis of words in context/co-text relation using a concordancing program. The paper compares the answers of both groups to determine the most problematic entries (incorrect answers), and to provide the possible reasons for them. Further, contextual clues are taken into consideration as a helpful source for determining correct entries, and tested with the concordancing program. Besides the emphasis on the usefulness of such gap-fill exercises combined with corpus for the development and enrichment of academic vocabulary, the paper also emphasizes the importance of guiding students in how to search for different grammatical and other contextual clues to make correct inferences, and how to use concordances to support or reject the claims.
Keywords: angleščina; English; tuji jeziki; znanstveni jezik; znanstveno besedišče; akademsko besedišče; korpusna lingvistika; Corpus linguistics; visokošolsko poučevanje; didactic method; didaktika